2015
DOI: 10.1378/chest.15-0169
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes Are Similar in ARDS Diagnosed by Oxygen Saturation/F io 2 Ratio Compared With Pao 2 /F io 2 Ratio

Abstract: BACKGROUND:Oxygen saturation as measured by pulse oximetry/F io 2 (SF) ratio is highly correlated with the Pa o 2 /F io 2 (PF) ratio in patients with ARDS. However, it remains uncertain whether SF ratio can be substituted for PF ratio for diagnosis of ARDS and whether SF ratio might identify patients who are systemically diff erent from patients diagnosed by PF ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 33 publications
2
121
0
3
Order By: Relevance
“…It is also possible that differences in ventilator management strategies account for the difference in mortality. 29 Our study has limitations, most importantly the fact that the included ABG data were the result of routine clinical ABG testing, with the associated risk of …”
Section: Resultsmentioning
confidence: 97%
“…It is also possible that differences in ventilator management strategies account for the difference in mortality. 29 Our study has limitations, most importantly the fact that the included ABG data were the result of routine clinical ABG testing, with the associated risk of …”
Section: Resultsmentioning
confidence: 97%
“…In these patients, the SpO 2 /FiO 2 ratio was used as a surrogate marker to diagnose hypoxemia. The SpO 2 /FiO 2 ratio is a noninvasive way to evaluate oxygenation and has been shown to have diagnostic utility in people, particularly in children with ARDS, in whom arterial blood sampling can be challenging . Preliminary evaluation of the SpO 2 /FiO 2 ratio in dogs found that this ratio correlated well with the PaO 2 /FiO 2 ratio in a population of dogs requiring assessment of oxygenation .…”
Section: Discussionmentioning
confidence: 99%
“…Adult critically ill patients were included in VALID if they remained in the ICU for at least 2 days and were excluded if they had a history of severe chronic lung disease or were admitted for uncomplicated overdose [12, 13]. Informed consent was obtained for sample collection from the patients or their designated surrogates; if patients or surrogates were unable to provide consent, the institutional review board granted a waiver of consent.…”
Section: Methodsmentioning
confidence: 99%